THE FOLKLORE NARRATIVES AND SYMBOLIC RELATIONS OF THE PEACOCK AND PEACOCK FEATHERS (Philological Studies, 2022)
The semantic relations manifested in myth, ritual, and visual narratives can be detected in many folkloristic manifestations and forms. As an example, we will point out the appearance of the peacock, as an archaic animal, a symbol of divinity, royal insignia, and supreme spiritual achievements manifested in Macedonian and Balkan folklore. During the analysis of the semantic function of a pound,  we shall mention the peacock feathers worn on the head by girls and fiancees from Macedonia, including Lazar`s girls – as part of their ritual costume. Furthermore, we shall look at the specific silver or another type of female metal jewelry that is part of the festive female costume as headgear, usually given to them by their fiancee. The semantic relationship between the peacock, the flowers, and the vine can also be traced in the skirts of girls and brides from the region of Mavrovo in which they appear as archetypal cosmogonic symbols of virginity, fertility, and immortality - a phenomenon that we find in antiquity, but also in the wider cultural area, as symbols of the highest insignia and divinity. The series of examples including early Christian iconography, for which more examples from Macedonia are indicated, testify to the continuity of the appearance of this bird in these areas. The importance of this bird is illustrated by a series of folk songs, as well as the use of peacock feathers in ritual magic. We also show the symbolism of the peacock in the esoteric teachings of Europe, as a symbol of the final phase of the internal transformation and improvement of man, which corresponds to its exceptional importance in the cultures developed in the East.